2014
DOI: 10.1038/ejhg.2014.213
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-recessive SASH1 variants associated with a new genodermatosis with pigmentation defects, palmoplantar keratoderma and skin carcinoma

Abstract: 9SASH1 (SAM and SH3 domain-containing protein 1) is a tumor suppressor gene involved in the tumorigenesis of a spectrum of solid cancers. Heterozygous SASH1 variants are known to cause autosomal-dominant dyschromatosis. Homozygosity mapping and whole-exome sequencing were performed in a consanguineous Moroccan family with two affected siblings presenting an unclassified phenotype associating an abnormal pigmentation pattern (hypo-and hyperpigmented macules of the trunk and face and areas of reticular hypo-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 36 publications
5
44
0
1
Order By: Relevance
“…We found that SASH1 knockdown increase both proliferation and migration in HAECs. This result is in accordance with the literature, as SASH1 knockdown increases proliferation and migration in various human cancer cell lines 104,109,108 , and a SASH1 variant (c.1849G>A; p.Glu617Lys) increases proliferation of human fibroblasts 115 . In accordance with our proliferation results, CCND1 and CCND3 were found to be up-regulated at the protein level following SASH1 knockdown.…”
Section: Figure 16 Mass Spectrometry Identification Of Sash1 Partnersupporting
confidence: 81%
See 2 more Smart Citations
“…We found that SASH1 knockdown increase both proliferation and migration in HAECs. This result is in accordance with the literature, as SASH1 knockdown increases proliferation and migration in various human cancer cell lines 104,109,108 , and a SASH1 variant (c.1849G>A; p.Glu617Lys) increases proliferation of human fibroblasts 115 . In accordance with our proliferation results, CCND1 and CCND3 were found to be up-regulated at the protein level following SASH1 knockdown.…”
Section: Figure 16 Mass Spectrometry Identification Of Sash1 Partnersupporting
confidence: 81%
“…Recently, SASH1 expression has been linked to a number of diseases such as pre-ecclampsia 149 , Alzheimer disease 150 , colorectal and breast cancer 133,135,136 , skin carcinoma 151 and Dyschromatosis universalis hereditaria (DUH) 141 . While little is known about the role of SASH1 in the vascular physiopathology, an in vitro study has reported SASH1 to be up-regulated following VEGF receptor blockade in human pulmonary microvascular endothelial cells 152 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example represents the influence of RHBDF2 variants on EGFR signalling [145]. In the case of SASH1 mutations, wound-healing assays on control and patient-derived fibroblasts were performed to reveal alterations in pathways governing cell migration [146]. It is anticipated that functional evidence will play an increasingly important role in CRC research.…”
Section: Guidelines For Gene Discoverymentioning
confidence: 99%
“…The SAM domain can exhibit more complex functions in these protein-protein interaction domains (15). The SAM domain mediates protein-protein interactions through homologous and heterologous oligomerization with the SAM domains of other proteins, and it can mediate Smaug protein and mRNA binding to facilitate transcriptional regulation (16,17). SASH1 is a member of a recently described family of SH3/SAM adapter molecules according to its domain structure, thus suggesting a role in signaling pathways (18).…”
Section: Introductionmentioning
confidence: 99%